Spatial-Structural Relations among Technology Industrial Clusters: A Comparative Analysis of Metropolitan Regions in the U.S - Rajendra Kulkarni; Jean Paelinck; Roger Stough (European Regional Science Association (ERSA), 2001)
Technical industrial clusters are defined and analyzed for a sample of U.S. metropolitan regions. Economic structure, spatial proximity and shape of the clusters are examined across the metropolitan regions through various economic and spatial measures and statistics. The data for this research are used to test the hypothesis that close spatial proximity results in stronger economic functional interdependence. This hypothesis is examined and the implications of the test are explored.
Keywords: 330